The Importance of Role Ambiguity and Role Conflict in Completing Employee Job Satisfaction - Andari Andari (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of role ambiguity on employee job satisfaction, the effect of role conflict on employee job satisfaction, and the effect of role ambiguity and role conflict on employee job satisfaction. The object of this research is the BUMN (State Owned Enterprise) company PT PLN (persero) UPDL Suralaya. The method used in this study is descriptive quantitative using observation techniques, interviews and through questionnaires given to employees as well as secondary data collection. The analytical tool used to test the hypothesis is IBM SPPS V22. The sampling method used is a saturated sample of 35 respondents . The analysis technique used is instrument test, classical assumption test, multiple linear regression analysis, coefficient of determination, partial t test, and simultaneous F test. Partial research results conclude that there is a positive and significant effect of role ambiguity on Employee Job Satisfaction, and not there is an influence of Role Conflict variables on Employee Job Satisfaction . The results of the study simultaneously show that the value of F count > F table ( 17.200 > 3.285) thus Ho is rejected and Ha is accepted with a significant level of 0.000 <0.05 so it can be concluded that there is a significant influence between Role Ambiguity (X1) and Role conflict (X2) ) on Employee Job Satisfaction (Y).